Kyrgyz Republic : sixth review under the three-year arrangement under the Extended Credit Facility, staff report, and press release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
"On April 3, 2014, parliament approved a new government, led by Mr. Otorbaev, the new Prime Minister. The ministers of economy and finances kept their positions. Moreover, on May 7, 2014, a new chairperson was appointed for the National Bank of the Kyrgyz Republic (NBKR). No major changes in economic policies are expected. In February 2014, parliament approved a new deal with Centerra, ending a two-year dispute over the Kumtor gold mine. Background. In the first quarter, growth moderated to 5.6 percent (year-on-year) after the 2013 growth spike at 10.5 percent related to an unexpectedly high level of gold production. In the same period, inflation picked up slightly, owing to depreciation of the som in response to pressures from the depreciation of the Russian ruble and the devaluation of the Kazakh tenge. The NBKR intervened heavily to mitigate these pressures, but has recently rebuilt reserves to ensure a more comfortable level of over three months of imports. The current account is expected to deteriorate this year because of higher imports related to large public investments and FDI-financed infrastructure projects. Fiscal performance in 2013 was better than expected, with a deficit of 4 percent of GDP, but revenue headwinds call for a cautious budget in 2014. The medium-term outlook remains broadly favorable, provided prudent macroeconomic policies continue and are supported with structural reforms, including tax policy and administration reforms, public financial management (PFM) reforms, and implementation of FSAP recommendations, in particular the Banking Code. Program. The program is broadly on track, with all end-December 2013 quantitative performance criteria and all but one indicative targets (IT) met for end-December 2013. Although three March 2014 ITs were missed, since then there has been progress in rebuilding reserves and enhancing tax collections. The two structural benchmarks (SBs) for end-December were met, and the SB on signing the contract with one of the big four audit companies to audit the Debt Resolution Agency (DEBRA) is expected to be completed with delay. The remaining SB on introducing the Treasury Single Account (TSA) on a pilot basis was missed. Overall, the Kyrgyz authorities are completing a broadly successful three-year ECF arrangement, although further reforms will be needed to preserve and deepen the accomplishments. Despite occasional domestic political turmoil, the authorities have regained and maintained macroeconomic stability, consolidated the fiscal position, implemented a new monetary framework, and embarked on a comprehensive banking sector reform. The authorities have not yet expressed their intentions regarding a successor program"--Abstract
RELATIONS WITH THE ASIAN DEVELOPMENT BANK (ADB)RELATIONS WITH THE EUROPEAN BANK FOR RECONSTRUCTION AND DEVELOPMENT (EBRD); TECHNICAL ASSISTANCE PROVIDED BY THE FUND; STATISTICAL ISSUES.
Online resource; title from pdf title page (IMF Web site, viewed July 14, 2014).
"July 2014."
"June 11, 2014"--Page 2 of pdf
Keywords: International Monetary Fund -- Kyrgyzstan; International Monetary Fund; Economic development -- Kyrgyzstan; Fiscal policy -- Kyrgyzstan; Transmission mechanism (Monetary policy) -- Kyrgyzstan; Structural adjustment (Economic policy) -- Kyrgyzstan; Economic indicators -- Kyrgyzstan; Economic development; Economic indicators; Fiscal policy; Structural adjustment (Economic policy); Transmission mechanism (Monetary policy); Kyrgyzstan